Characterization of the Affective Component of Acute Postoperative Pain Associated with a Novel Rat Model of Inguinal Hernia Repair Pain. (10th December 2015) - Bree, Dara; Moriarty, Orla; Broom, Daniel C.; Kelly, John P.; Roche, Michelle; Finn, David P.
Summary: Aims: Acute postoperative pain remains a significant healthcare issue. Historically, the assessment of postoperative pain in rodents has relied on evoked withdrawal or reflexive measures. Using a recently developed, anatomically relevant rat model of acute postoperative pain (J Pain, 16, 2015, 421), the present experiments sought to investigate the affective component of acute postoperative pain associated with inguinal hernia repair. Methods: Male Lister hooded rats underwent surgery to model Lichtenstein inguinal hernia repair (without hernia induction), or a sham procedure. Postsurgical characterization involved a modified place escape/avoidance paradigm (mPEAP), as well as home cage and open field locomotor activity monitoring. In pharmacological validation studies, rats received either morphine or carprofen prior to mPEAP testing. Results: Surgery was associated with a significantly increased proportion of the trial duration in the light compartment of the mPEAP arena, in avoidance of the noxious stimulus, compared with sham animals. When retested in the mPEAP at day 7 postsurgery, there was no difference between sham and surgery animals for time spent in either compartment, but surgery animals displayed a persistent increase in the percentage response to noxious stimulation. Morphine and carprofen treatment in surgery animals reduced escape/avoidance behavior at discrete time points over the trial. Surgery‐induced reductions in home cage and open field locomotor activity were also observed. Conclusion: The present studies report for the first time the characterization of the affective component of acute postoperative pain using the mPEAP in a rodent model, which may facilitate development of improved understanding and treatment of postoperative pain.